2020
DOI: 10.3390/jcm9020305
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 2 Deficiency Promotes Neuroinflammation and Pain Behaviors Following Nerve Injury in Mice

Abstract: Microglia, the resident macrophages, act as the first and main form of active immune defense in the central nervous system. Arginase 2 (Arg2) is an enzyme involved in L-arginine metabolism and is expressed in macrophages and nervous tissue. In this study, we determined whether the absence of Arg2 plays a beneficial or detrimental role in the neuroinflammatory process. We then investigated whether the loss of Arg2 potentiated microglia activation and pain behaviors following nerve injury-induced neuropathic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The correlation between neuropathic pain and microglia is well established, with strong evidence of both morphological and pathological mechanisms of disease [7]. In the spinal nerve ligation (SNL) rat model, the microglia in the dorsal horn of the spinal cord showed significant changes in morphology and in the number of spots staining with specific microglial markers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between neuropathic pain and microglia is well established, with strong evidence of both morphological and pathological mechanisms of disease [7]. In the spinal nerve ligation (SNL) rat model, the microglia in the dorsal horn of the spinal cord showed significant changes in morphology and in the number of spots staining with specific microglial markers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Arg2 is a mitochondrial protein involved in arginine metabolism; however, we and other investigators have shown that its role in macrophages goes beyond its enzymatic activity and places Arg2 as a key player in the resolution of the inflammatory response in these innate immune cells. 7 , 25 , 26 Therefore, increasing Arg2 levels in macrophages could represent an alternative route for the treatment of inflammatory disorders. The over-expression of proteins could be achieved in multiple ways, for example, by using viral vectors 27 or by optimizing mechanisms at the post-transcriptional level, including mRNA degradation by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also observed a generalized decrease of other pro-inflammatory cytokines such as IL-6 and TNF upon treatment with Arg2 TSB. The biological mechanisms behind this broader effect are unknown; however, Arg2 knock-out mice have previously reported to have higher TNF-α levels compared with wild type (WT) in response to Helicobacter pylori infection 25 and express higher mRNA levels of IL-1β as well as Nos2 (which leads to production and secretion of the pro-inflammatory mediator nitric oxide) in a model of nerve injury, 26 while the over-expression of Arg2 led to a decrease of inducible nitric oxide protein levels in LPS-stimulated RAW 264.7 cells. 31 This evidence collectively suggests a pleiotropic role for Arg2 in cytokines secretion and inflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide which is produced by L-arginine catalyzed by nitric oxide synthase, is a small, highly soluble and diffusible free radical, which is an important signal molecule between nerve cells. As a neuronal synthase, nNOS has been proved to play a role in neuropathic pain by generous studies [37,38]. In peripheral nerve injury, NMDAR [39,40] is activated in advance to promote the opening of Ca 2+ channel [41], and then activate nNOS to synthesize NO.…”
Section: Discussionmentioning
confidence: 99%